Effects of cellular membranes and the precore protein on hepatitis B virus core particle assembly and DNA replication - Yu-Chen Chuang; Jing-hsiung James Ou (mBio)
ABSTRACT Hepatitis B virus (HBV) core particle is critical for the transport and replication of the viral DNA genome. By characterizing HBV core particles in different subcellular compartments, we found that when the HBV core protein was expressed by itself, it formed core particles with a uniform and fast mobility on a non-denaturing agarose gel. However, when the core protein was expressed from a replication-competent 1.3mer HBV genome, it formed particles with more heterogeneous structures. The presence of the precore protein, a protein related to the core protein, led to the formation of chimeric particles in the cytoplasm that consisted of both precore and core proteins. When the precore protein was expressed by itself, it could also form particulate structures in association with cellular RNAs in the nucleus. Our further analysis revealed that, in cells with replicating HBV, only the fast-migrating core particles on the gel contained the viral RNA and DNA, and the membrane-associated core particles contained more mature HBV DNA than the cytosolic core particles. In addition, the precore protein reduced the level of core particle-associated HBV DNA. Interestingly, the precore protein level in the cells could be increased by the degradative autophagy inhibitor bafilomycin A1 but not by the proteasome inhibitor MG132, suggesting that autophagy might regulate the biological activities of the precore protein. In conclusion, our results indicated that membranes and the precore protein could regulate HBV core particle assembly and DNA replication and suggested a role of autophagy in the regulation of HBV precore protein activities.IMPORTANCEHepatitis B virus (HBV) is an important human pathogen that chronically infects 254 million people in the world. This virus contains a core particle, which plays an important role in the transport and replication of the viral DNA genome. The major protein constituent of this particle is the viral core protein. In this report, we examined how the subcellular compartments and the related precore protein might affect the core particle structure and viral DNA replication. We found that the subcellular localizations could affect the core particle assembly, and membranes and the precore protein could regulate HBV DNA replication. We also found that the inhibition of autophagic degradation increased the precore protein level, suggesting a role of autophagy in the regulation of precore protein activities. These findings provided important information for further understanding the HBV life cycle, which will aid in the development of novel drugs for the treatment of HBV patients.